Neopatriarchy : a Theory of Distorted Change in Arab Society. - Sharabi, Hisham (Oxford University Press, 1992)
This study argues that the historical patriarchal authority structure of the Middle East has not succumbed to modernization and disappeared or even been fundamentally revised. Instead, it lives on as neopatriarchy: a patriarchal authority that has frozen political and social development.